2017
DOI: 10.1016/j.devcel.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cilia Signaling Shapes the Development of Interneuronal Connectivity

Abstract: Summary Appropriate growth and synaptic integration of GABAergic inhibitory interneurons are essential for functional neural circuits in the brain. Here, we demonstrate that disruption of primary cilia function following the selective loss of ciliary GTPase Arl13b in interneurons impairs interneuronal morphology and synaptic connectivity, leading to altered excitatory/inhibitory activity (E/I) balance. The altered morphology and connectivity of cilia mutant interneurons and the functional deficits are rescued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 89 publications
6
99
1
Order By: Relevance
“…Within the adult CNS, dysfunction of ciliary trafficking is linked to retinal degeneration (Wheway et al, 2014), and conditional loss of the ciliary protein ARL13B from mouse striatal interneurons both during their development as well as in the mature brain, results in changes in their morphology and connectivity (Guo et al, 2017). Our work extends these findings and provides additional strong evidence that primary cilia and signals mediated by these organelles are important to maintain the morphology of neurons as well as their connections.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Within the adult CNS, dysfunction of ciliary trafficking is linked to retinal degeneration (Wheway et al, 2014), and conditional loss of the ciliary protein ARL13B from mouse striatal interneurons both during their development as well as in the mature brain, results in changes in their morphology and connectivity (Guo et al, 2017). Our work extends these findings and provides additional strong evidence that primary cilia and signals mediated by these organelles are important to maintain the morphology of neurons as well as their connections.…”
Section: Discussionsupporting
confidence: 69%
“…Nevertheless, newly emerging evidence suggests that cilia and ciliary signaling may be important in this context: Cilia are required for the establishment of synaptic connectivity in hippocampal dentate granule neurons (Kumamoto et al, 2012) and in striatal interneurons (Guo et al, 2017). Neuronal cilia also concentrate a wide array of GPCRs and other neuropeptide and neurotrophin receptors important for complex neurological functions (Berbari et al, 2008;Domire et al, 2011;Green et al, 2012;Guadiana et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…SSTR3 and SSTR5 were similarly strongly co-localised with all types of interneurons and this co-localisation ranged from 74 to 97%. Some authors have shown that in mouse and rat, SSTR3 is selectively targeted to primary neuronal cilia, a specialised microtubule-based organelle that play a role in neuronal signaling and the regulation of synaptic connectivity (Handel et al 1999;Whitfield 2004;Guo et al 2017). We detected SSTR3 in membrane and cytoplasm of neuronal cell bodies and dendrites, while observing the cilia-like shapes as well.…”
Section: Discussionmentioning
confidence: 60%
“…These phenotypes are in line with the neurodevelopmental and GABAergic hypotheses of schizophrenia. In addition, primary cilium signaling is required for postmigration developmental processes in interneurons, such as connectivity and circuit activity (Guo et al, ). In fact, selective loss of a ciliary‐specific GTPase in interneurons alters GABAergic neuronal morphology and synaptic connectivity, therefore, altering excitatory/inhibitory activity balance (Guo et al, ).…”
Section: Neurodevelopmental Disorders Associated To Bloc‐1 and Borc Cmentioning
confidence: 99%
“…In addition, primary cilium signaling is required for postmigration developmental processes in interneurons, such as connectivity and circuit activity (Guo et al, ). In fact, selective loss of a ciliary‐specific GTPase in interneurons alters GABAergic neuronal morphology and synaptic connectivity, therefore, altering excitatory/inhibitory activity balance (Guo et al, ). This unbalance in excitatory/inhibitory activity is a central mechanism of neurodevelopmental disorders and it is a phenotype shared by Bloc1s8 sdy/sdy and other mouse models of neurodevelopmental disorders (Gogolla et al, ; Carlson et al, ; Yizhar et al, ).…”
Section: Neurodevelopmental Disorders Associated To Bloc‐1 and Borc Cmentioning
confidence: 99%